Product Development Strategy of Duftende Indonesia - Hogiana, Della Yunia; Dellyana, Dina (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Running a business certainly is not that easy, there are many obstacles and challenges that exist, one of which is to improve the performance of the company itself by constantly innovating and delivering the best products to customers. And this study aims to find what are the idea of perfume product which is desirable by customer. To reach this objective, Buyers Persona and also Pearson’s New Product Development Process used in this study as the basic knowledge of research and used as the main construct in predicting what kind of perfume product that desired by the customer. This research uses qualitative research method by semi-structured interview with twenty respondents to asking for their opinion on product development based on Pearson's New Product Development Process. The results of this data will determine what are the idea of perfume product which is desirable by customer, what hat are the suitable buyer persona for the product, also what are the suitable business strategy for the product, and what are the acceptance of the new product which is developed.Keyword : New Product Development Strategy; Beauty Product; Perfume